Letter from Charles F. Chandler to the Henry H. Otters Manufacturing Company. - Chandler, Charles Frederick (1911)
Charles F. Chandler (1836-1925) writes to the Henry H. Otters Manufacturing Company to discuss calculations concerning the proportion of arsenic in food dye. Chandler was an American Chemist known for his work in public health as a keen public health advocate and sanitation reformer. He also is a founder of the American Chemical Society and held many professional and public leadership roles throughout his career.
Keywords: Dyes and dyeing; Arsenic; Arsenic--Toxicology; Dyes and dyeing--Toxicology; Chandler, Charles Frederick, 1836-1925